2016
DOI: 10.21873/invivo.10998
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Morus alba Leaf Extract on N-Nitrosodiethylamine-induced Hepatocarcinogenesis in Rats

Abstract: Abstract. Background Since primary liver cancer is the third leading cause of cancer mortality worldwide, chemopreventive strategies aimed at reducing its risk or delaying its onset are highly desirable. The most common type of primary liver cancer is an inflammation-associated cancer developing from hepatocytes, hepatocellular carcinoma (HCC). Hepatocarcinogenesis progresses from chronic intrahepatic inflammation within the state of oxidative stress, which results in continuous cellular injury, necrosis and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Among other phenolic acids (GAL, PRO, VAN, FER, SIN) conditioning lowered the CHL and CAF extract concentration. It has been shown that CHL was also dominant in aqueous extracts from other varieties of WML [1,14] and acetone extract from WML-P [6].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other phenolic acids (GAL, PRO, VAN, FER, SIN) conditioning lowered the CHL and CAF extract concentration. It has been shown that CHL was also dominant in aqueous extracts from other varieties of WML [1,14] and acetone extract from WML-P [6].…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…WML products consumed with a diet are thought to protect against liver cancer, to prevent obesity-related non-alcoholic fatty liver, hypolipidemic or lipid-regulating properties in blood protect against atherosclerosis, to show anti-aggregative properties in platelet and anti-inflammatory effects or to reduce anxiety [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic properties of white mulberry leaves (WML) have previously been utilized in the Far East Medicine. Presently, apart from gardening and forestry, they have been applied in food production (PRZEOR & FLACZYK, 2016;ZOU, 2015), as they are non-toxic to the human organism (KUJAWSKA et al, 2016). Positive outcomes of WML consumption have been demonstrated with regard to, among others, diabetes, hyperlipidemia, eye and skin diseases, obesity, atherosclerosis, liver cancer (BUTT et al, 2008;IQBAL et al, 2012;QIN et al, 2013).…”
mentioning
confidence: 99%
“…M. alba L. has been used worldwide in traditional medicine for the treatment of various diseases from ancient times to the present ( 12 , 15 ). Previous studies have indicated that M. alba L. possesses various pharmacological properties, including antimicrobial ( 16 ), antioxidant ( 17 ), antitumor ( 18 ), anti-obesity ( 19 ), antihypotensive ( 20 ), neuroprotective ( 21 , 22 ), and antidiabetic ( 23 , 24 ) actions. In addition, our previous studies indicated that the extracts and components of M. alba L. fruit water extract were safe ( 25 ), immunostimulatory ( 10 , 12 , 26 ), and had indirect anticancer activity by enhancing immune responses mediated by TLR4 signaling ( 12 ).…”
Section: Discussionmentioning
confidence: 99%